2021
DOI: 10.1161/strokeaha.120.031672
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Outcome in Stroke Patients With Acute M2 Occlusion and Minor Neurological Deficits

Abstract: Background and Purpose: Treatment in stroke patients with M2 segment occlusion of the middle cerebral artery presenting with mild neurological deficits is a matter of debate. The main purpose was to compare the outcome in patients with a minor stroke and a M2 occlusion. Methods: Consecutive intravenous thrombolysis (IVT) eligible patients admitted to the Bernese stroke center between January 2005 and January 2020 with acute occlusion of the M2 segment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…Mean age, percentage of men or women, comorbidity (eg, atrial fibrillation), and median NIHSS score were not available because almost all of the included studies were not designed to explore the effect of EVT on specific vessel occlusion sites and we only retrieved the subset of data from these studies for the purpose of this meta-analysis. Only one study provided the percentage of patients who were treated after 2015 and this study showed that 111 out of 169 patients (65.7%) were treated after 2015, and mRS 0–1 at 3 months was not significantly different between the EVT versus IVT groups in mild ischemic stroke due to distal M2 occlusions 24…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Mean age, percentage of men or women, comorbidity (eg, atrial fibrillation), and median NIHSS score were not available because almost all of the included studies were not designed to explore the effect of EVT on specific vessel occlusion sites and we only retrieved the subset of data from these studies for the purpose of this meta-analysis. Only one study provided the percentage of patients who were treated after 2015 and this study showed that 111 out of 169 patients (65.7%) were treated after 2015, and mRS 0–1 at 3 months was not significantly different between the EVT versus IVT groups in mild ischemic stroke due to distal M2 occlusions 24…”
Section: Resultsmentioning
confidence: 82%
“…Pooled results showed that EVT compared with BMM was not associated with a significantly higher rate of symptomatic ICH in proximal ICA or M1 occlusions (5.1% vs 3.1%; OR 1.71, 95% CI 0.61 to 4.81),10 12 but was associated with a higher rate of symptomatic ICH in distal M2 occlusions (6.8% vs 2.3%; OR 3.44, 95% CI 1.42 to 8.32),10 12 24 and the effect of EVT in the proximal ICA or M1 versus distal M2 occlusions was not significantly different (P for interaction=0.31, I 2 =18%) (online supplemental eFigure 2).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Other results suggested that intravenous thrombolysis might also be associated with deterioration due to thrombus fragmentation in some patients with ICA occlusion (22). The efficacy of bridging thrombolysis in those patients also remains to be elucidated (23). Those results underline the necessity to select the right patient for the right treatment.…”
Section: Discussionmentioning
confidence: 98%